Global, regional and national burden of ischemic heart disease and its attributable risk factors from 1990 to 2021: a systematic analysis of the Global Burden of Disease study 2021 - Leyuan Yang; Bo Zheng; Yanjun Gong (BMC Cardiovascular Disorders)
Abstract Background Ischemic heart disease (IHD) continues to be the foremost contributor to global morbidity and mortality. This analysis aims to report an updated assessment of prevalence, deaths, and disability-adjusted life years (DALYs) due to IHD and its attributable risk factors in 204 countries and territories from 1990 to 2021, by age, sex, and socio-demographic index (SDI). Methods This analysis used data from the Global Burden of Diseases, Injuries, and Risk Factors Study 2021. IHD was defined as acute myocardial infarction, chronic stable angina, chronic IHD, and heart failure due to IHD. Major indicators used in this study were prevalence, death and DALYs. All estimates were reported as absolute counts and age-standardized rates per 100,000 population, along with their 95% uncertainty intervals (UIs). Results Globally, IHD accounted for 254.3 (95%UI: 221.4 to 295.5) million prevalent cases, 9.0 (95%UI: 8.3 to 9.5) million deaths and 188.4 (95%UI: 177.0 to 198.1) million DALYs in 2021. There was a noticeable decline in the global age-standardized death rate (ASDR) [-31.6% (95%UI: -34.9 to -28.3)] and age-standardized DALYs (ASRDALYs) [-28.8% (95%UI: -32.5 to -25.2)] from 1990 to 2021, with an estimated annual percentage change of -1.3 (95%CI: -1.34 to -1.26) and − 1.2 (95%CI: -1.25 to -1.16), respectively. In 2021, the global prevalence, death, and DALY rates of IHD were higher among males across all age groups, while death and DALY rates reaching a peak in the oldest group for both sexes. Regionally, we found a nonlinear but negative association between age-standardized prevalence rate (ASPR) and SDI. Nationally, similar negative associations were observed between ASRDALYs and SDI. High systolic blood pressure and high low-density lipoprotein cholesterol were the factors contributing most to the deaths and DALYs due to IHD. Conclusions Despite declining global age-standardized death and DALYs rates of IHD, sustained multilevel prevention strategies remain essential. This requires population-wide risk factor reduction, targeted interventions for high-risk populations, and strengthened community healthcare networks to ensure accessible, guideline-based management.